The Road of Lost Innocence: อำนาจของเรื่องเล่า - Chantrasupawong, Narumol (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The Road of Lost Innocence is translated from French language. It is about the life of a Khmer woman Somaly Mam, once a prostitute who later became one of the activists fighting sexual slavery. She was one of the founding members of an organization which has rescued, rehabilitated and reintegrated thousands of women and children. She has also been the recipient of several awards. The Road of Lost Innocence reveals the power of narrative. It matches with the West’s expectation of the East (Cambodia) and the western cultural code. It also confirms the ‘myth’ the West has about the East.